DIVERSIFICATION OF INNOVATIVE MEASURES AT GAS DISTRIBUTION COMPANIES OF UKRAINE IN THE CONTEXT OF EUROPEAN EXPERIENCE (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article revealed the essence and importance of energy security in the context of the European integration policy, reviewed the activities of gas distribution enterprises of Ukraine in conditions of transformational changes, the necessity of prioritizing their development towards European priority community, describes the main trends flow of innovative institutions competing in the European gas market, with 'innovation is found out understanding of the functioning of the European gas market, options specified imp lementatsiyi European experience innovative mechanisms in the domestic gas market. The review of innovative mechanisms to improve the competitiveness of the energy market in Europe and proposed uniform implementation of innovative ways to diversify gas distribution activities at enterprises of Ukraine.
Keywords: diversification, innovative measures, gas market, competitive principles, ecodesign impact, transformational shifts, tariff formation